Microfinance Training on MSMEs In Klatak Tourism Village Facing the Covid-19 Pandemic (Universitas Negeri Semarang, 2022)
Covid-19 has paralyzed the world economy, including Indonesia. Indonesian people can still not face the economic downturn due to the Covid-19 pandemic. Microfinance management for MSME actors in Indonesia is increasingly essential, especially in a pandemic like the current one. Therefore, Microfinance training is needed so MSME actors can survive amid a sluggish economy. This community service program partners with the Masyarakat Peduli Wisata Klatak (Makladuta). The method used is Community Service Workshop. This activity is also in collaboration with the Department of Management FE Unnes, which has made Makladuta a partner. Service activities are carried out online through zoom meetings and Youtube streaming on Tuesday, August 10, 2021. The resource person for the activity is the Head of the Central Java Province Cooperatives and SMEs Office, Dra. Ema Rachmawati, M. Hum., which describes the material on